Analysis and design of an unbalanced input three phase controlled rectifier - Islam Khan, Shahidul; Mohd. Yatim, Abdul Halim; Nik Idris, Nik Rumzi (IEEE, 1997)
Controlled Rectifier like all other power electronics converters are usually designed to work in balanced input condition. Evaluation of real operating conditions, however, shows that this assumption is not true in many cases. It is, therefore, necessary that converter analysis should be carried out considering unbalanced condition. Ilks paper discusses a novel technique to produce near perfect d c output from a three phase controlled rectifier when the three input phase voltages are amplitude unbalanced. This paper also focuses on the analysis, design and performance characteristics of' the three phase controlled rectifier. Finally analytically predicted results are verified by simulation.